Exploring natural convection and heat transfer dynamics of Al2O3-H2O nanofluid in a modified tooth-shaped cavity configuration - Bijan Krishna Saha; Jahidul Islam Jihan; Goutam Barai; Nur Jahangir Moon; Goutam Saha; Suvash C. Saha (International Journal of Thermofluids)
Background: Heat transfer (HT) is crucial in engineering, particularly for thermal management systems, where elements like a heated rectangular wall, an adiabatic circular cylinder, and nanofluids introduce complexity and improvements. Additionally, exploring the impact of magnetic forces on natural convection (NC) is important in various industrial processes.Aims: The purpose of the study is to examine how different factors influence HT and fluid flow within the cavity. This includes examining the roles of the heated rectangular vertical wall (RVW), the adiabatic circular cylinder, and the magnetic force on the NC of Al2O3H2O nanofluid.Method and validations: This study solves the governing equations and corresponding boundary conditions using Galerkin's weighted residual-based finite element methods. Also, comprehensive comparisons and validations against existing results are conducted to ensure the accuracy of the findings.Parameters: The study involves a range of parameter values, including 0 ≤ nanoparticle volume fraction (φ) ≤ 5 %, 104 ≤ Rayleigh number (Ra) ≤ 106, 0 ≤ Hartmann number (Ha) ≤ 60.Results: The research reveals that insulated wavy top wall and heated RVW significantly shape the flow field and heat transport. The presence of the adiabatic cylinder further enhances this phenomenon. Incorporating Al2O3-H2O nanofluid enhances HT performance, especially at larger φ.Conclusion: The study concludes that the innovative design approach involving the wavy top wall, heated RVW, and adiabatic circular cylinder significantly influences the heat transfer and flow field within the cavity. This design effectively mitigates external heat loss, demonstrating its potential for improved thermal management systems.